Current status and future perspectives on molecular and serological methods in diagnostic mycology. (November 2009) - Lau, Anna; Chen, Sharon; Sleiman, Sue; Sorrell, Tania
Invasive fungal infections are an important cause of infectious morbidity. Nonculture-based methods are increasingly used for rapid, accurate diagnosis to improve patient outcomes. New and existing DNA amplification platforms have high sensitivity and specificity for direct detection and identification of fungi in clinical specimens. Since laboratories are increasingly reliant on DNA sequencing for fungal identification, measures to improve sequence interpretation should support validation of reference isolates and quality control in public gene repositories. Novel technologies (e.g., isothermal and PNA FISH methods), platforms enabling high-throughput analyses (e.g., DNA microarrays and Luminex ®® xMAP™™) and/or commercial PCR assays warrant further evaluation for routine diagnostic use. Notwithstanding the advantages of molecular tests, serological assays remain clinically useful for patient management. The serum Aspergillus galactomannan test has been incorporated into diagnostic algorithms of invasive aspergillosis. Both the galactomannan and the serum ββ-D -glucan test have value for diagnosing infection and monitoring therapeutic response.